Effectiveness of the educational training program for Japanese chief residents: A one‐year pilot study - Toshinori Nishizawa; Kazuya Nagasaki; Kazuki Tokumasu; Shunsuke Kosugi; Tadayuki Hashimoto; Kosuke Tanaka; Koma Hotta; Sho Isoda; Aiko Harada; Shinya Ishigame; Takuma Hata; Masayuki Nogi (Journal of General and Family Medicine)
Abstract Background Multi‐institutional faculty development programs for chief residents were lacking in Japan. This study evaluated the effectiveness of the program for enhancing the knowledge and behaviors of chief residents at the national level. Methods Six participants completed self‐assessment questionnaires at three points: before, immediately after, and 6 months post‐program. Knowledge and behavior changes were compared using the Mann–Whitney U test. Results Significant improvements in knowledge were observed and maintained at 6 months. However, behavioral changes were limited, with significant improvements only in counseling skills. Conclusion The program effectively increased knowledge but faced challenges in translating it into sustained behavioral change.